2021
DOI: 10.1002/jcv2.12027
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent well‐being amid the COVID‐19 pandemic: Are girls struggling more than boys?

Abstract: Background: Differential effects of the coronavirus SARS- pandemic and associated public restrictions on adolescent girls and boys are emerging but have not been elucidated. This study examined gender differences across broad indicators of adolescent well-being during the COVID-19 pandemic in Iceland, and explored potential explanations for these differences. Methods:In total, 523 youth (56.5% girls) born in Iceland in 2004 completed measures on mental health problems (depressive symptoms, anger and suicide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
67
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 49 publications
12
67
1
6
Order By: Relevance
“…It was found that adolescent girls had lower well-being and a higher risk of depression during the pandemic. These results are in line with the most recent studies [2,3,12,26] as well as with most of the pre-pandemic large-scale epidemiological studies [11,39]. Moreover, female youngsters in our study were less physically active and reported a longer duration of sedentary behavior, which was also prominent in other studies showing that girls in adolescence usually exhibited less healthy lifestyle also during pre-pandemic times [11,22].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It was found that adolescent girls had lower well-being and a higher risk of depression during the pandemic. These results are in line with the most recent studies [2,3,12,26] as well as with most of the pre-pandemic large-scale epidemiological studies [11,39]. Moreover, female youngsters in our study were less physically active and reported a longer duration of sedentary behavior, which was also prominent in other studies showing that girls in adolescence usually exhibited less healthy lifestyle also during pre-pandemic times [11,22].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, recreational screen time and overall sedentary behavior had significantly increased during the lockdown due to COVID-19 [ 13 , 23 , 25 ], and it was associated with more psychosomatic complaints, more depressive symptoms, and lower life satisfaction both in pandemic [ 13 , 26 ] and pre-pandemic [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identity reorientation following the traumatic experience ( Halldorsdottir et al, 2021 ). In the younger age group, the theme of identity in development clearly emerges.…”
Section: Construction Of An Intervention Modelmentioning
confidence: 99%